2016
DOI: 10.1177/1756283x16642190
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell-based therapies in inflammatory bowel disease: promises and pitfalls

Abstract: Inflammatory bowel disease (IBD) is a chronic, often relapsing, condition that deeply impacts the quality of life for many patients. Although there have been significant advances in medical treatments, a large proportion of patients become refractory to available therapeutic options. Stem-cell therapy through hematopoietic stem cells (HSCs) or mesenchymal stem (stromal) cells (MSCs) is a promising therapeutic option for severe refractory cases especially when surgery is not feasible. In HSC transplantation, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 116 publications
0
23
0
Order By: Relevance
“…However, staining for α-SMA, a marker of differentiated MSC, demonstrated that, at least in UC, the majority of PD-L1 expressing cells were identified as myofibroblasts. Further, the reduction of PD-L1 in CD may serve as a scientific rationale for the use of “PD-L1 competent” MSCs for the treatment of perianal CD where the major objective is to deposit these stem cells locally in fistulizing tracts to suppress the local inflammatory responses ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, staining for α-SMA, a marker of differentiated MSC, demonstrated that, at least in UC, the majority of PD-L1 expressing cells were identified as myofibroblasts. Further, the reduction of PD-L1 in CD may serve as a scientific rationale for the use of “PD-L1 competent” MSCs for the treatment of perianal CD where the major objective is to deposit these stem cells locally in fistulizing tracts to suppress the local inflammatory responses ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transplant data from 2013 show that over 320,000 patients have received either autologous or allogeneic stem-cell transplants for various indications. 14,15 There are only a few studies reporting mesenchymal stem cell transplantation (MSCT) in IBD patients, especially in UC and several publications about MSCT in patients with pyoderma gangrenosum, but not in combination ogf these diseases. [16][17][18] In this clinical case we tried to analyze some peculiarities of clinical course in patient with UC and PG the consequences of standard treatment algorithm and MSCT applied for this patient.…”
Section: Discussionmentioning
confidence: 99%
“…Transplantation of HSCs and MSCs have shown beneficial effects in treating certain types of CD in clinical trials (Forbes et al, ; Hawkey, ; Panés et al, ), although they are believed to mainly possess immunomodulatory actions (Duran & Hommes, ; Okamoto & Watanabe, ). Nonetheless, MSCs appear indirectly to be able to promote epithelial repair by contributing to the ISCs' niche and by regulating claudin expression in TJs (Tanaka et al, ; Yabana et al, ).…”
Section: Re‐establishing Epithelial Barrier Integrity By Means Of Stementioning
confidence: 99%